A new species of Deuveia Minet, 2002 (Lepidoptera, Epicopeiidae) from China - Krupitsky, Anatoly V.; Shapoval, Nazar A. (Zootaxa, 2020)
A new epicopeiid species, Deuveia panda sp. n., is described from northeastern Sichuan, China. The new species differs from the sole congeneric species, D. banghaasi (Hering, 1936), in the remarkable black and white colouration pattern of the wings, the shape of the wings and the shape of the valva, juxta and aedeagus. The new species is geographically isolated from all known localities of D. banghaasi by highlands of the Min Mountains.